Konsep Karamah dalam Masyarakat Islam (Konstruksi dan Implikasi Sosial Keagamaan Kewalian Abu Ibrahim Woyla di Aceh) - Putri Nailul Muradi (Program Studi Sosiologi Agama Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri Ar-Raniry, Banda Aceh, Indonesia, 2021)
This study aims to describe the construction and socio-religious implications of Abu Ibrahim Woyla in Aceh. The method used is qualitative with data collection through interviews and literature studies relevant to the research objectives. The results showed that the Acehnese acknowledged the existence of waliyullah in Islam, and they believe that Abu Ibrahim Woyla is a scholar close to Allah, so he has reached the